Accreditation of private midwifery and nursing schools in Mali: a local sustainable solution to increasing the supply of qualified health workers - Cheick Oumar Touré; Sujata Bijou; Melanie Joiner; Andrew Brown; Jeanne Tessougué; Hamada Maiga; Fatoumata Dicko; Abdel Kader Keïta (BMC, 2021)
Abstract Background The World Health Organization's Global Strategy on Human Resources for Health (HRH) emphasizes the importance of dynamic and effective health worker regulation for achieving the health-related Sustainable Development Goals, with the establishment of education standards and quality assurance of education programs being critical. Governments in West Africa have struggled to address the problems within their higher education systems for health professionals, and it is now generally acknowledged that private institutions can play a crucial role in revitalizing the region's outdated universities. However, the rapid expansion of private schools raises concerns about the quality of education and adequacy of regulatory mechanisms. The USAID-funded Mali HRH Strengthening Activity, led by IntraHealth International, assisted Mali's Ministry of Health and Social Development to deliver targeted HRH interventions to improve the quality of education in private universities, better manage available health workers, and initiate a decentralized strategy for health worker recruitment and motivation. Case presentation In 2018, the HRH activity leveraged the West African Health Organization (WAHO)'s accreditation system to support 10 private nursing schools to introduce WAHO's regionally accepted, competency-based curriculum in reproductive, maternal, newborn, and child health. The project undertook a 10-step process to work alongside private nursing and midwifery schools to assess their current status against WAHO regional standards, implement action plans to address identified gaps, and support the institutions toward accreditation. As a result, eight schools in Mali are now accredited compared to only three at project inception. Conclusions This case study underscores the importance of private school accreditation in Mali to improve the quality of health worker training through a standardized local curriculum. By supporting existing regulatory bodies that oversee accreditation, local capacity for initial accreditation of private nursing schools has been increased. Engaging universities in a partnership that shows the benefits of accreditation while maintaining a focus on the need to protect communities is critical to success. If the global community is to meet the WHO's predicted health worker shortfall, then private education providers will need to be part of the solution. Robust and engaging health worker education accreditation systems are an essential part of that future.